BALANCING CONSUMER RIGHTS AND BUSINESS INTERESTS IN ONLINE CROSS-BORDER CONSUMER CONTRACTS - ten Wolde, Mathijs H. (Journal of Central Banking Law and Institutions, 2022)
Protection of consumers as weaker parties is an important goal in Indonesian society and in Indonesian law. The same applies to the EU Member States. When it comes to crossborder consumer contracts, special rules are needed to ensure this goal can still be achieved. In this regard the European Union developed rules on jurisdiction and applicable law which apply both to situations exclusively connected with EU Member States and to international situations connected with third countries. The Brussels I Regulation pursues an objective of legal certainty which consists in strengthening the legal protection of persons established in the European Union, by enabling the applicant to easily identify the court in which he may sue and the defendant reasonably to foresee before which court, he may be sued. The Rome I Regulation does the same for the law regulating the protection of the consumer. This way both the aims of protection of the weaker consumer and legal certainty on the side of the commercial party go hand in hand. Where legal certainty is an important precondition for international trade and thus for a nation’s economy, clear rules are needed. By presenting the EU rules in the dynamics of the caselaw of the European Court of Justice, this article aims to contribute to the discussion on how future cross-border consumer protecting regulations could be shaped in Indonesia and ASEAN.